Undifferentiated pleomorphic sarcoma in the maxillary sinus: a case report - Seyed Hosein Tabatabaei; Alireza Navabazam; Mohammad amin Yektaie; Farinaz Sabaghzadegan (Journal of Medical Case Reports)
Abstract Background Undifferentiated pleomorphic sarcoma, previously called malignant fibrous histiocytoma, is a type of malignant mesenchymal tumor (sarcoma) of soft tissue and sometimes bone. It is uncommon in the oral cavity and very sporadic in the maxillary sinus. Microscopic diagnosis of this malignancy in the maxillary sinus can be very challenging, because there is a range of features that may overlap with other benign and malignant tumors. Case presentation In this paper, we report a case of undifferentiated pleomorphic sarcoma in the maxillary sinus of a 61-year-old Iranian man who was referred to the maxillofacial surgery ward due to pain and swelling of the upper jaw and visual problems in the right eye. In the initial incisional biopsy, peripheral giant cell granuloma was diagnosed in the hospital service. Yet, on request of the surgeon, during reviewing the slides in the oral pathology service of the School of Dentistry, and using an immunohistochemical method, undifferentiated pleomorphic sarcoma was diagnosed. In this paper, a case of undifferentiated pleomorphic sarcoma in the maxillary sinus is reported, with an emphasis on the management of its problems and diagnostic errors. Conclusion This study reviews the challenges and histopathological diagnostic errors of this uncommon tumor in this rare location. This lesion may be similar to other malignant tumors, and its correct diagnosis requires a detailed and complete examination.